Antitumor and immunomodulatory activities of total flavonoids extract from persimmon leaves in H(22) liver tumor-bearing mice - Chen, Li (Sci Rep, 2018)
Persimmon (Diospyros kaki L.) leaves are commonly used in Asia as tea infusion and as an agent in traditional medicine. The present study aims to explore the antitumor and immunomodulatory effects of total flavonoids extract from persimmon leaves (PLF) in H(22) liver tumor-bearing mice. We found that the PLF showed significant inhibition on the liver tumor growth in mice with a tumor inhibition rate of up to 49.35%. In contrast to the severe side effects of cyclophosphamide (CTX), the PLF exhibited anti-cachexia effect and showed no alternation in the body weight and food intake in mice. Moreover, compared with the vehicle control and CTX group, the PLF significantly enhanced the thymus and spleen indices, level of serum interleukin-18 (IL-18), monocyte/macrophage phagocytosis, level of serum hemolysin, and activity of natural killer (NK) cells. This study demonstrated that the PLF could effectively inhibit liver tumor growth in vivo via enhancement of the immune function in mice, and it displayed the potential to be a safe and effective anticancer agent or functional immune-enhancing agent.